Insights Into the Effect of Rice Stripe Virus P2 on Rice Defense by Comparative Proteomic Analysis - Yang, Zihang; Zhang, Hehong; Tan, Xiaoxiang; Wei, Zhongyan; Wen, Caiyi; Sun, Zongtao; Sun, Bingjian; Chen, Jianping (Frontiers in Microbiology, 2022)
Rice stripe virus (RSV) has a serious effect on rice production. Our previous research had shown that RSV P2 plays important roles in RSV infection, so in order to further understand the effect of P2 on rice, we used Tandem Mass Tag (TMT) quantitative proteomics experimental system to analyze the changes of protein in transgenic rice expressing P2 for the first time. The results of proteomics showed that a total of 4,767 proteins were identified, including 198 up-regulated proteins and 120 down-regulated proteins. Functional classification results showed that differentially expressed proteins (DEPs) were mainly localized in chloroplasts and mainly involved in the metabolic pathways. Functional enrichment results showed that DEPs are mainly involved in RNA processing and splicing. We also verified the expression of several DEPs at the mRNA level and the interaction of a transcription factor (B7EPB8) with RSV P2. This research is the first time to use proteomics technology to explore the mechanism of RSV infection in rice with the RSV P2 as breakthrough point. Our findings provide valuable information for the study of RSV P2 and RSV infection mechanism.